The metaphorical rise of entrepreneurship - Cardow, Andrew (Massey University. Department of Management and International Business, 2006)
The words that have come to be associated with innovative and creative business enterprises – entrepreneur, entrepreneurship and entrepreneurial – have their English origins in the realm of armed conflict. However over time the terms were colonised by the commercial world with the result that by the end of the 20th century the terms have become firmly embed within the language of commerce. Yet along the way the meaning attached to the terms have become disassociated with commerce. By the start of the 21st Century the term entrepreneurial has become a metaphor, a stand in for innovation, creativity, proactivity and risk. It is argued that such a metaphor is not owned by the commercial world and instead is a figure of speech that can be used in any situation where the speaker requires a conceptual word to mean innovation, risk, proactivity and creativity.
Keywords: Metaphor; Entrepreneurship; Interpretation; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management